Conservative Treatment of Medial Meniscus Tear Through Ayurveda: A Case Study - Mahesh Sharma; Sourabh Deshmukh; Nitika Senger (Journal of Clinical and Diagnostic Research)
Meniscal tears are common knee injuries caused by acute trauma in younger individuals and degenerative changes in older adults, often linked to osteoarthritis. The menisci play a crucial role in shock absorption, load distribution, and knee joint stability. In Ayurveda, meniscal tears can be correlated with Sira Snayu Gata Vata (vascular and ligamentous disorder). A 47-year-old male presented with pain, swelling, tenderness, and restricted movement in the right knee for six months. He was advised to undergo Magnetic Resonance Imaging (MRI) investigation by a physician, which revealed a medial meniscus tear in the right knee joint. In clinical examinations, the McMurray test, Apley grind test, and the bounce home test were positive. Ayurvedic treatments, including Shodhan (bio-purification) and Shaman (palliative) therapies, were administered as an alternative to corticosteroids, aimed at reducing potential complications. This study evaluates the effectiveness of Ayurvedic treatment and rehabilitation strategies in improving functional outcomes for meniscal tears. In cases of medial meniscus injury, meniscectomy is often performed surgically. This case study demonstrates significant improvement in the assessment parameters of medial meniscus tears with Ayurvedic treatment and rehabilitation therapies, highlighting their potential as a non-invasive therapeutic approach for meniscal injuries.